Learners' Perspectives of the Train-the-Trainer Program in Creating the Role of Classroom Trainer - Susan B. Slusarski (Adult Education Research Conference, 1999)
Learners in train-the-trainer courses typically are presented with prescriptive content, yet the classroom setting is dynamic. This study examined the meaning participants in three train-the-trainer programs gave to the role of classroom trainer.